Molecular Design, Synthesis and Evaluation of 2,3-Diarylquinoxalines as Estrogen Receptor Ligands - Sangi, Diego P.; Cominetti, Marcia R.; Becceneri, Amanda B.; Resende, Flavia A. [UNESP]; Varanda, Eliana A. [UNESP]; Montanari, Carlos A.; Paixao, Marcio W.; Correa, Arlene G. (Bentham Science Publ Ltd, 2015)
Selective Estrogen Receptor Modulators (SERMs) are characteristically capable of being antagonist and agonist of estrogen receptors and, therefore, they can inhibit or stimulate estrogen production in different tissues. Aiming to contribute to the identification of new synthetic SERMs candidates, the basic skeletons of raloxifene and tamoxifene were used as model. Here of, a set of 2,3-diaryl-quinoxalines having 2-(piperidin-1-yl) ethanol in the side chain have been synthesized and evaluated against human mammary carcinoma cells estrogen dependent (MCF-7), as well as in recombinant yeast assays (RYA) expressing estrogen receptor. Compound LSPN332 showed 40% inhibition of MCF-7 and EC50= 290.6 mu M in RYA. The efficient synthesis of 2,3-diarylquinoxalines represents an excellent opportunity to identify new SERMs, and should therefore be of interest to the medicinal chemistry community.
Keywords: Ligand- and target-based molecular design; 2,3-diarylquinoxalines; estrogen receptor; SERMs; synthesis